Disentangling Immediate Adaptive Introgression from Selection on Standing Introgressed Variation in Humans. (6th December 2017) - Jagoda, Evelyn; Lawson, Daniel J; Wall, Jeffrey D; Lambert, David; Muller, Craig; Westaway, Michael; Leavesley, Matthew; Capellini, Terence D; Mirazón Lahr, Marta; Gerbault, Pascale; Thomas, Mark G; Migliano, Andrea Bamberg; et al.
Abstract: Recent studies have reported evidence suggesting that portions of contemporary human genomes introgressed from archaic hominin populations went to high frequencies due to positive selection. However, no study to date has specifically addressed the postintrogression population dynamics of these putative cases of adaptive introgression. Here, for the first time, we specifically define cases of immediate adaptive introgression (iAI) in which archaic haplotypes rose to high frequencies in humans as a result of a selective sweep that occurred shortly after the introgression event. We define these cases as distinct from instances of selection on standing introgressed variation (SI), in which an introgressed haplotype initially segregated neutrally and subsequently underwent positive selection. Using a geographically diverse data set, we report novel cases of selection on introgressed variation in living humans and shortlist among these cases those whose selective sweeps are more consistent with having been the product of iAI rather than SI. Many of these novel inferred iAI haplotypes have potential biological relevance, including three that contain immune-related genes in West Siberians, South Asians, and West Eurasians. Overall, our results suggest that iAI may not represent the full picture of positive selection on archaically introgressed haplotypes in humans and that more work needs to be done to analyze the role of SI in the archaic introgression landscape of living humans.